2019
DOI: 10.3390/ma12101607
|View full text |Cite
|
Sign up to set email alerts
|

Mode I Interlaminar Fracture of Glass/Epoxy Unidirectional Laminates. Part I: Experimental Studies

Abstract: The paper presents experimental tests of unidirectional double cantilever beams made of a glass fiber reinforced (GFRP) laminate. The critical value of the strain energy release rate (c-SERR or GIC), i.e., the mode I fracture toughness of the considered material was determined with three different methods: the compliance calibration method (CC), the modified compliance calibration method (MCC), and the corrected beam theory (CBT). Due to the common difficulties in precise definition of delamination initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Due to this, the authors have not compared the present FE result of mode I fracture energy with any existing literature. But the trend of the variation of reaction vs. displacement curve of the present advanced CNT/epoxy composite are similar in nature to the conventional glass/epoxy unidirectional laminated composite as reported by Samborski et al [15]. Elastic properties and mode I fracture energy of CNT/epoxy and CF/epoxy laminated composite have been calculated and then compared.…”
Section: Mode-i Fracture Energy Of the Cnt/epoxy And Cf/epoxy Laminatsupporting
confidence: 79%
“…Due to this, the authors have not compared the present FE result of mode I fracture energy with any existing literature. But the trend of the variation of reaction vs. displacement curve of the present advanced CNT/epoxy composite are similar in nature to the conventional glass/epoxy unidirectional laminated composite as reported by Samborski et al [15]. Elastic properties and mode I fracture energy of CNT/epoxy and CF/epoxy laminated composite have been calculated and then compared.…”
Section: Mode-i Fracture Energy Of the Cnt/epoxy And Cf/epoxy Laminatsupporting
confidence: 79%
“…This distinction is made since in the static tests the displacement increases constantly and has no direct influence. For this reason, any drop in force corresponds to a change in the stiffness of the specimen caused by glass fibre breakage or delamination as it has been shown in [ 39 , 42 , 44 , 47 ]. In contrast, the displacement and force changes cyclically in the dynamic tests, so the ratio of both should be constant over time.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in both cases the time can be determined by applying the threshold technique, only the determination of the healthy state and the corresponding reference value must be determined for each individual laminate. In summery, the complete failure detection in static test scenarios is going hand in hand with the results of the literature using carbon fibre-reinforced plastic [ 39 , 42 , 43 , 44 ], while the dynamic results going along with the results from Saeedifar et.al [ 45 ]. Consequently, the hypotheses H1 and H4 are confirmed, as it has been sufficiently demonstrated that both the damage index I and the standard deviation of the SED are applicable to determine the time of complete failure.…”
Section: Discussionmentioning
confidence: 99%
“…This form of material deterioration is understood as interlaminar cleavage that can be studied within the framework of Fracture Mechanics, as 2D or 3D crack initiation and propagation [ 11 , 12 , 13 ]. This demands the determination of fracture toughness with standardized procedures, providing globally the three classical fracture modes [ 14 , 15 , 16 , 17 ], which may be a demanding task when atypical layups come into play, for example those evoking elastic couplings [ 18 ]. In any case, damage detection, monitoring and identification is possible with contemporary experimental methods supported by appropriate modelling techniques, such us the Finite Element Method (FEM) and analytical solutions.…”
Section: Introductionmentioning
confidence: 99%